Mechanical behavior of cold recycled asphalt mixtures. - Kuchiishi, André Kazuo (2019)
The Brazilian reduced paved road density, the increasingly demand for highways, and the lack of investment in preventive maintenance practices accelerate the occurrence of pavement distresses. This imparts for poor riding quality highways, resulting in higher fuel consumption, greater emission of pollutant gases, and increasing operational costs. In this scenario, cold recycling practices may be a cost-effective and environmental friendly alternative for pavement rehabilitation. The cold recycled asphalt mixtures (CRAMs) produced by cold recycling techniques, are comprised by reclaimed asphalt pavement (RAP), bitumen stabilized agents (asphalt emulsion or foamed asphalt), and active fillers (cement or hydrated lime). Despite the economical and sustainable benefits, the CRAMs exhibit a complex mechanical behavior since numerous variables can influence its stiffness. Therefore, the purpose of this study is to evaluate the CRAM\' stiffness dependency regarding temperature, load frequency, stress-state and moisture content variation. Four types of CRAMs were collected from the field during experimental test section construction and were evaluated by means of laboratory tests. For temperature evaluation, the CRAMs linear viscoelastic properties were investigated by means of dynamic modulus and the results were used as input data for computational simulation. It was observed that the CRAMs viscoelastic properties influence the pavement mechanical response. For moisture evaluation, triaxial resilient modulus tests were conducted at different curing conditions. In conjunction with the filter paper test and X-ray micro computed tomography, a correspondence was observed between matric suction and resilient modulus. Besides, the CRAMs stress-state dependency was evaluated by means of pavement simulation and compared with in situ measurements. It was observed that the non-linear elastic behavior of CRAMs substantially influences the pavement mechanical behavior.